2007
DOI: 10.1200/jco.2006.10.0909
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Morbidity in Cancer: Spouse Caregivers

Abstract: Spouse caregivers of patients with advanced cancer are a high-risk population for depression. Subjective caregiving burden and relational variables, such as caregivers' attachment orientations and marital dissatisfaction, are important predictors of caregiver depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
398
5
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(443 citation statements)
references
References 45 publications
(3 reference statements)
28
398
5
12
Order By: Relevance
“…9 In keeping with these findings, some of the previous studies on depression after a diagnosis of cancer in a spouse support an association, [10][11][12][13] whereas others have reported negative or null findings. [14][15][16] The majority of the studies had several limitations, including small sample sizes of spouses with cancer (<200 subjects), [10][11][12][13][14][15][16] and only a few small studies did include a relevant comparison group. 12,13 To the best of our knowledge, none of the previous studies regarding the risk of depression in partners of cancer patients used an objectively defined state of depression, diagnosed years before the study was conducted, and obtained from an administrative, population-based and nationwide database to reduce the risk for misclassification of the outcome under study as well as recall and information bias.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…9 In keeping with these findings, some of the previous studies on depression after a diagnosis of cancer in a spouse support an association, [10][11][12][13] whereas others have reported negative or null findings. [14][15][16] The majority of the studies had several limitations, including small sample sizes of spouses with cancer (<200 subjects), [10][11][12][13][14][15][16] and only a few small studies did include a relevant comparison group. 12,13 To the best of our knowledge, none of the previous studies regarding the risk of depression in partners of cancer patients used an objectively defined state of depression, diagnosed years before the study was conducted, and obtained from an administrative, population-based and nationwide database to reduce the risk for misclassification of the outcome under study as well as recall and information bias.…”
mentioning
confidence: 56%
“…34 Two follow-up studies also demonstrated a significantly increased risk of depression among individuals whose partner had cancer in the terminal stage. 10,15 Thus, the effect of breast cancer in a partner on the man's risk for hospitalization with depression might depend both on the burden of late effects of the breast cancer and treatment and the overall prognosis. 15 Previously, we conducted a nationwide, populationbased study to determine whether cancer is followed by an increased risk of divorce or separation in cohabiting partners, which might explain the increased risk of severe depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that the degree to which the attitudinal and behavioral changes take place depends on the stage of cancer (Butler et al, 2005;Braun et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, research has primarily focused on the individual adjustment of women to the disease. Psycho-oncology researchers have begun to emphasize the need to analyze this disease within the family context and specifically in the context of marital relationships only in the past two decades (Braun, Mikulincer, Rydall, Walsh, & Rodin, 2007;Carlson et al, 2000;Manne & Badr, 2008;O'Mahoney & Carroll, 1997). Since this research emerged, several studies have examined the influence of cancer on marital relationships (e.g., Dorval at al., 2005;Hegerdoon, Sanderman, Coyne, Bolks, & Tuinstra, 2008) and have thus enabled a deeper and more comprehensive knowledge regarding the functioning of couples in this context (Hegerdoon et al, 2008;Manne & Badr, 2008;O'Mahoney & Carroll, 1997).…”
Section: Introductionmentioning
confidence: 99%